2004
DOI: 10.1097/00061198-200406000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Results of Trabeculectomy in Primary Congenital Glaucoma with and without the Use of Mitomycin C

Abstract: The success of trabeculectomy for primary congenital glaucoma with mitomycin C was not different than that of trabeculectomy with mitomycin C in the studied patients. Mitomycin C was associated with a higher incidence of complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
2
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 28 publications
0
25
2
1
Order By: Relevance
“…24,47 Antimetabolites such as mitomycin C or 5-fluorouracil can be applied to prevent excessive scar formation; however, some authors report a higher risk of complications in the paediatric population compared to adults. [48][49][50] Postoperative complications after AVI include hypotony (IOPp5 mm Hg) (11-42%), shallow anterior chamber (15 B26%), tube malposition (5B26%), tubecorneal touch (3B8%), tube occlusion (14%), tube exposure (6B12%), and other rare complications such as tenon encapsulated cyst (1B7%), postoperative cataract (0B2%), strabismus (0B3%), retinal or choroidal detachment (1B18%), endophthalmitis (1B5%), wound leak (3%), plate migration (2%), inflammation, hyphema, delayed retrobulbar haemorrhage. [28][29][30]33,39,51,52 In our study, overall rates of complications was lower than previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…24,47 Antimetabolites such as mitomycin C or 5-fluorouracil can be applied to prevent excessive scar formation; however, some authors report a higher risk of complications in the paediatric population compared to adults. [48][49][50] Postoperative complications after AVI include hypotony (IOPp5 mm Hg) (11-42%), shallow anterior chamber (15 B26%), tube malposition (5B26%), tubecorneal touch (3B8%), tube occlusion (14%), tube exposure (6B12%), and other rare complications such as tenon encapsulated cyst (1B7%), postoperative cataract (0B2%), strabismus (0B3%), retinal or choroidal detachment (1B18%), endophthalmitis (1B5%), wound leak (3%), plate migration (2%), inflammation, hyphema, delayed retrobulbar haemorrhage. [28][29][30]33,39,51,52 In our study, overall rates of complications was lower than previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…There have been few reports on the use of Mitomycin-C (MMC) during trabeculectomy in childhood glaucoma. [12][13][14][15][16] Despite achieving good results with the use of MMC, it is not recommendable its use in children with early postnatal period because long-term results and complications of MMC use are not yet known.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Primary congenital glaucoma is the most common of the childhood glaucomas. 4 A variety of surgical procedures have been used for the treatment of primary congenital glaucoma, including goniotomy (for cases of clear cornea), 5 trabeculotomy, 6 trabeculectomy, 3,7,8 and glaucoma drainage devices. 8 The use of wound-modulating agents, including antimetabolites such as 5-flourouracil and mitomycin C, has added to the success of filtering surgery in pediatric glaucoma.…”
Section: Introductionmentioning
confidence: 99%
“…8 The use of wound-modulating agents, including antimetabolites such as 5-flourouracil and mitomycin C, has added to the success of filtering surgery in pediatric glaucoma. 3,7,9 Of particular interest, lately the procedures for primary congenital glaucoma are combined, 10,11 especially trabeculotomy-trabeculectomy with mitomycin C, with variably reported success rates. 1,11,12 Childhood glaucoma is more common and more severe in communities with higher consanguineous marriages, such as in Romanian Gypsies and in the Saudi Arabian population.…”
Section: Introductionmentioning
confidence: 99%